UNDERSTANDING TEXTILE WASTE MANAGEMENT IN PUNE DISTRICT: A DESCRIPTIVE APPROACH - Athalye, Sheetal; Atre, Avadhut (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The management of textile waste poses a significant challenge, especially in urban and semi-urban areas like the Pune district, due to its environmental and social implications. There is a growth in population by 30.37% each year, which is directly related to the textile waste generated each year in Pune District (Mundhe et al., 2014). Therefore, there is a need for proper waste collection and transportation routes to protect the environment from hazardous waste disposal. This study aims to examine the generation, categorization, and current management strategies for textile waste in the Pune District. Through descriptive analysis, the research seeks to identify significant trends and underlying challenges in this area. Data was collected through surveys and secondary sources, offering insights into the volume of waste generated, textile consumption, methods of disposal, the behavior of consumers towards waste and the role of the stakeholders in waste management is analyzed in this study. The development of further solutions for the waste is generated. The results reveal that the majority of textile waste remains improperly managed, contributing significantly to landfill accumulation. The exact data for textile consumption and waste is also unknown due to waste management process followed in Pune District. Additionally, awareness about recycling and sustainable waste management practices among stakeholders was found to be low, indicating a pressing need for targeted educational and infrastructural interventions. Consumer awareness for textile waste management should also be raised. Future research should concentrate on developing waste management strategies to enhance waste disposal practices. Sustainable solutions like upcycling, recycling should be used by the stakeholders to reduce the accumulation of waste.